Spread‐out Bragg peak proton FLASH irradiation using a clinical synchrocyclotron: Proof of concept and ion chamber characterization. Issue 8 (11th July 2021) - Darafsheh, Arash; Hao, Yao; Zhao, Xiandong; Zwart, Townsend; Wagner, Miles; Evans, Tucker; Reynoso, Francisco; Zhao, Tianyu
Abstract: Purpose: The purpose of this work is to (a) demonstrate the feasibility of delivering a spread‐out Bragg peak (SOBP) proton beam in ultra‐high dose rate (FLASH) using a proton therapy synchrocyclotron as a major step toward realizing an experimental platform for preclinical studies, and (b) evaluate the response of four models of ionization chambers in such a radiation field. Methods: A clinical Mevion HYPERSCAN ® synchrocyclotron was adjusted for ultra‐high dose rate proton delivery. Protons with nominal energy of 230 MeV were delivered in pulses with temporal width ranging from 12.5 μs to 24 μs spanning from conventional to FLASH dose rates. A boron carbide absorber and a range modulator block were placed in the beam path for range modulation and creating an SOBP dose profile. The radiation field was defined by a brass aperture with 11 mm diameter. Two Faraday cups were used to determine the number of protons per pulse at various dose rates. The dosimetric response of two cylindrical (IBA CC04 and CC13) and two plane‐parallel (IBA PPC05 and PTW Advanced Markus ® ) ionization chambers were evaluated. The dose rate was measured using the plane‐parallel ionization chambers. The integral depth dose (IDD) was measured with a PTW Bragg Peak ® ionization chamber. The lateral beam profile was measured with EBT‐XD radiochromic film. Monte Carlo simulation was performed in TOPAS as the secondary check for the measurements and as a tool for further optimization of the range modulators' design. Results: Faraday cups measurement showed that the maximum protons per pulse is 39.9 pC at 24 μs pulse width. A good agreement between the measured and simulated IDD and lateral beam profiles was observed. The cylindrical ionization chambers showed very high ion recombination and deemed not suitable for absolute dosimetry at ultra‐high dose rates. The average dose rate measured using the PPC05 ionization chamber was 163 Gy/s at the pristine Bragg peak and 126 Gy/s at 1 cm depth for the SOBP beam. The SOBP beam range and modulation were measured 24.4 mm and 19 mm, respectively. The pristine Bragg peak beam had 25.6 mm range. Simulation results showed that the IDD and profile flatness can be improved by the cavity diameter of the range modulator and the number of scanned spots, respectively. Conclusions: Feasibility of delivering protons in an SOBP pattern with >100 Gy/s average dose rate using a clinical synchrocyclotron was demonstrated. The dose heterogeneity can be improved through optimization of the range modulator and number of delivered spots. Plane‐parallel chambers with smaller gap between electrodes are more suitable for FLASH dosimetry compared to the other ion chambers used in this work. Abstract :